Simulation of industrialised building system formation for housing construction - Zainal Abidin@Md. Taib, Ahmad Razin (2007)
Industrialised Building System (IBS) is a construction method that offers economisation of design, site work and materials, provides shorter construction time, saving in labour, better quality control, immunity to weather changes and the most importantly, the cost factor. It has been proven successful in some countries such as Finland, Denmark, Netherlands, Singapore, England and the United States (CIDB, 1998). In our country Malaysia, the shorter construction time offered by IBS may seems to be the solution for the housing demand in Malaysia. The aim of this study is to determine the process flow of housing construction that are applying Industrialized Building System (IBS) components for its main structure. For that purpose, sequence process of installation activities for construction of IBS houses has been identified. Witness 2001 simulation software has been applied to model a construction of 300 IBS houses. The most achievable completion time has been examined and at the same time optimum resources for the construction has been identified during the simulation analysis. It is hoped that the widespread understanding on the Industrialised Building System (IBS) can further help to develop and promote IBS as an innovative construction method in Malaysia.